Measurements in an Outdoor Facility and Numerical Simulation of the Radar Cross Section of Targets at 10 GHz - Guilherme G. Peixoto; Mauro Angelo Alves; Alberto José de Faro Orlando; Mirabel Cerqueira Rezende (Journal of Aerospace Technology and Management, 2011)
This paper presents preliminary data from an ongoing study on the radar cross section (RCS) of targets with simple and complex surface geometries (a flat square plate, a 90° dihedral corner reflector and a retired air-to-air missile). Measurements and computer simulations of these metallic targets were carried out at 10 GHz and also when the surfaces of the targets were completely coated with a radar absorbing material (RAM), consisting of flexible sheets of carbonyl iron dispersed in a silicone rubber matrix. Experimental measurements were obtained in an outdoor facility, and computer simulations were performed using a commercial software package. The main objective of this study was to compare results in order to highlight some of the issues related to the determination of the RCS of an actual target. Additionally, a Brazilian research institute has demonstrated the capability to produce and characterize materials related to the main aspects of RCS research, namely, measurement, simulation, and production of RAM. This paper introduces the reader to the research being carried out in this area at the Materials Division in the Instituto de Aeronáutica e Espaço.